Endowment or Discrimination? An Analysis of Immigrant-Native Earnings Differentials in Switzerland - Stefan M. Golder (Kiel Institute of World Economics (IfW), 2000)
Recent studies have shown that there are significant earnings differentials between immigrants and natives in Switzerland. The goal of this paper is to determine whether these differences can be attributed to diverging socio-economic endowments or to discrimination. We use the well-known econometric technique, developed by Oaxaca (1973) and Blinder (1973), to determine the extent of discrimination. As data on earnings are available only for employed, we adopt a two-stage Heckman procedure to correct for sample-selection bias. Our analysis is based on data from the 1995 wave of the Swiss Labor Force Survey (SLFS). The decomposition of the earnings differential reveals that the discrimination effect plays a more important role in the explanation of the earnings differential than the endowment effect.
Keywords: J61; J71; J31; F22; 330; International Migration; Wage Differentials; Immigrant Workers; Discrimination; Internationale Arbeitsmobilität; Ausländische Arbeitskräfte; Arbeitsmarktdiskriminierung; Lohndifferenzierung; Lohn; Humankapital; Schätzung; Schweiz